Stressed Liver and Muscle Call on Adipocytes with FGF21 - Luo, Yongde; McKeehan, Wallace L. (Frontiers in Endocrinology, 2013)
Fibroblast growth factor 21 (FGF21) is an emerging regulator of local and systemic metabolic homeostasis. Treatment with pharmacological levels of FGF21 alleviates obesity and associated metabolic diseases including diabetes. However, beyond antiobesogenic effects, the normal roles and underlying mechanisms of FGF21 as an endocrine hormone remain unclear. A recent wave of studies has revealed that FGF21 is a stress-induced endocrine factor in liver, muscle and other tissues that targets adipose tissue and adipocytes through FGFR1-betaKlotho (KLB) complex. Adipose tissues and adipocytes within diverse tissues respond with metabolites and adipokine signals that affect functions of body tissues systemically and cells within local microenvironment adjacent to adipocytes. Normally this is to prevent impaired tissue-specific function and damage to diverse tissues secreting FGF21 in response to chronic stress. Therefore, diverse stressed tissues and the adipose tissue and adipocytes constitute a beneficial endocrine and paracrine communication network through FGF21. Here we attempt to unify these developments with beneficial pharmacological effects of FGF21 on obesity in respect to inter-organ stress communication and mechanisms.